2018
DOI: 10.1155/2018/6598918
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Bacteria Associated with Cell Phones of Healthcare Professionals in Selected Hospitals in Saudi Arabia

Abstract: Cell phones may be an ideal habitat for colonization by bacterial pathogens, especially in hot climates, and may be a reservoir or vehicle in transmitting nosocomial infections. We investigated bacterial contamination on cell phones of healthcare workers in three hospitals in Saudi Arabia and determined antibacterial resistance of selected bacteria. A questionnaire was submitted to 285 healthcare workers in three hospitals, and information was collected on cell phone usage at the work area and in the toilet, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
30
9
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 26 publications
9
30
9
9
Order By: Relevance
“…As MPs are not sterile devices and are frequently touched by hands, all those tested in this study were shown to harbour saprophytic skin flora, especially coagulase negative staphylococci, whereas Gram-negative bacteria were far less frequently detected, as already described [ 33 ]. Our investigations focused on some bacteria that were shown to be responsible for severe healthcare-associated infections in French paediatric wards, including S. aureus , Gram-negative isolates [ 23 ] or more recently, S. capitis [ 26 ].…”
Section: Discussionsupporting
confidence: 69%
“…As MPs are not sterile devices and are frequently touched by hands, all those tested in this study were shown to harbour saprophytic skin flora, especially coagulase negative staphylococci, whereas Gram-negative bacteria were far less frequently detected, as already described [ 33 ]. Our investigations focused on some bacteria that were shown to be responsible for severe healthcare-associated infections in French paediatric wards, including S. aureus , Gram-negative isolates [ 23 ] or more recently, S. capitis [ 26 ].…”
Section: Discussionsupporting
confidence: 69%
“…In Bangladesh, research focused on the presence of multidrug-resistant bacteria on mobile phones of health workers reported that 50% of the S. aureus isolates were resistant to Ceftazidine (14). In a study in Saudi Arabia, bacteria was isolated from mobile phones of health care workers and tested against a panel of 12 antimicrobial agents, only one S. aureus isolate had Vancomycin heteroresistance after sensitivity testing (15). The same study also reported that 38.6% of the cell phones had been colonized…”
Section: Discussionmentioning
confidence: 99%
“…Así mismo, se ha identificado que el interés de los investigadores se ha orientado más recientemente a documentar la resistencia bacteriana a los fármacos de uso clínico. No obstante, esta variable no ha sido documentada en todos los estudios revisados, por lo que se propone para futuras revisiones abordar como eje central la multidrogorresitencia de las bacterias aisladas a partir de teléfonos celulares 48,49 . De igual forma, un elemento que vale la pena explorar en futuros estudios es la presencia de otros agentes tales como virus y hongos, entre otros, que pueden comportarse como patógenos nosocomiales de interés clínico presentes en los teléfonos celulares 10,50 .…”
Section: Duazaryunclassified